Operating room team safety and perioperative anesthetic management of patients with suspected or confirmed novel corona virus in resource limited settings: A systematic review. (October 2020) - Chekol, Wubie Birlie; Melesse, Debas Yaregal
Abstract: Background: Novel Corona Virus is a pandemic infectious disease which affects all age groups with higher incidence in geriatric population and chronic diseases. Contact, droplet and airborne had a role for transmission of the disease during airway manoeuvres in infected patients. This study aimed to prepare the operation room and provide protection of both the patient and health care personnel. Method: This systematic review was conducted according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) protocol. Search engines like Pub Med through HINARI, Cochrane database, Google Scholar to get access for current and updated evidences on operating room team safety and perioperative anesthetic management for patients with suspected or confirmed novel corona virus. Discussion: High risk procedures for aerosolization including endotracheal intubation, open lung surgery and airway suctioning should be managed with vented masks. Conclusion: All health care personnel should wear personal protective equipment based on the class of patients during surgery. Elective procedures should be postponed to save and mobilize resources for the protection and management of the pandemic disease. Emergency procedures including burn, Cesarean section, malignant neoplasia, perforated viscus and traumatic injury should be operated with wearing of personal protective equipment.